2000
DOI: 10.1109/55.852966
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cobalt silicidation on the low-frequency noise behavior of shallow p-n junctions

Abstract: This work describes the low-frequency noise of forward biased shallow p-n junctions fabricated in epitaxial silicon substrates. Particular emphasis is on the effect of silicidation on the low-frequency noise spectral density . It will be demonstrated that the observed 1 noise is significantly larger in Co-silicided junctions compared with the nonsilicided ones. A detailed analysis of the current and geometry dependence of leads to the conclusion that the 1 noise is of the generation-recombination (GR) type, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…An analysis of the measured data using the method described in Refs. 51,[60][61][62] shows that trap has a repulsive character due to the very small capture cross-section of 10 À20 cm 2 , and that its activation energy is equal to 0:47 eV. It should be noted that the capture cross-section in the case of the dielectric is typically several orders of magnitude smaller than for the bulk Si material trapping.…”
Section: Random Telegraph Signal Behavior Of Drain Currentmentioning
confidence: 93%
“…An analysis of the measured data using the method described in Refs. 51,[60][61][62] shows that trap has a repulsive character due to the very small capture cross-section of 10 À20 cm 2 , and that its activation energy is equal to 0:47 eV. It should be noted that the capture cross-section in the case of the dielectric is typically several orders of magnitude smaller than for the bulk Si material trapping.…”
Section: Random Telegraph Signal Behavior Of Drain Currentmentioning
confidence: 93%
“…This effect leads, in particular, to the fact that the center of the electron charge of the inversion layer is located not on the gate surface of the silicon film, but at a certain distance Z C away. In other words, the channel turns out to be displaced into the film interior by the distance Z C , which can reach 2 nm for sufficiently low values of V GF [27]. Such a displacement of the channel could explain the following feature of 1/f noise.…”
Section: /F Noisementioning
confidence: 98%
“…Considering the physical circumstances of the 1/f noise generation in submicron and decananometer MOS transistors, one should also mention the two-dimensional sampling of electrons in the channel [25][26][27][28]. This effect leads, in particular, to the fact that the center of the electron charge of the inversion layer is located not on the gate surface of the silicon film, but at a certain distance Z C away.…”
Section: /F Noisementioning
confidence: 99%
“…Individual charge traps can significantly alter the channel current of nm-sized FETs. At the same time, it has been observed that the capture kinetics of RTS in submicron FETs cannot be described by the wellknown Shockley-Read-Hall model, [1][2][3]8,9 in particular, at low currents and voltages.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] Now, it is commonly considered that the decisive factors determining the strong current dependence of s c are electron distribution (perpendicular to the Si/SiO 2 interface) dependent on the high electric field near the interface 9 and Coulomb blockade effect. [10][11][12] On the other hand, it is shown by Mueller et al…”
Section: Introductionmentioning
confidence: 99%